The new era in the treatment of deep vein occlusion - Kęsik, Jan Jakub; Terlecki, Piotr; Feldo, Marcin; Pietura, Radosław; Zubilewicz, Tomasz (Polish Journal of Public Health, 2015)
A non-invasive, conservative treatment has been a standard in treating acute and chronic deep vein thrombosis. This treatment turned out to be ineffective, particularly in the hip area. Also, it was demonstrated that it does not influence the frequency of manifestations of post-thrombotic syndrome. Previous attempts to surgically reconstruct deep veins, unlike arteries reconstruction, yielded no positive results and also increased hemorrhagic and embolic complications. Currently, alreadyin the period of the acute thrombosis of deep veins, the methods of early re-canalization, both with the application of targeted thrombolisis, as well as of pharmacomechanical methods, are applied.Thanks to a wide array of image examination methods applied in pre-operational and intra-operational diagnostics optimum, it is possible to plan a revascularising treatment in the sick individuals suffering from the already developed manifestations of the post-thrombotic syndrome.The development of endovascular methods, made possible thanks both to the surgeons’ experience in the re-canalization field, as well as constant improvements of stents dedicated to the venous system, allowed for effective use of these techniques in curing the occlusion of deep veins. It was the case with the arterial system and works here as well. Applying the hybrid proceeding, combining opened techniques and endovascular ones, works very well in selected cases.